IL-15 Harnesses Pro-inflammatory Function of TEMRA CD8 in Kidney-Transplant Recipients - Tilly, Gaëlle; Doan-Ngoc, Tra-My; Yap, Michelle; Caristan, Aurélie; Jacquemont, Lola; Danger, Richard; Cadoux, Marion; Bruneau, Sarah; Giral, Magali; Guerif, Pierrick; Nicol, Bryan; Garcia, Alexandra; et al. (Frontiers in Immunology, 2017)
The involvement of TEMRA CD8 is evident in a large array of immunological conditions ranging from auto- to allo-immunity. Nevertheless, the factors leading to their accumulation and activation remain ill-defined and efficient therapeutics to control their inflammatory response is lacking. Here, we show that IL-15-stimulated TEMRA from kidney transplant recipients promote inflammation by inducing the expression of CX3CL1 by endothelial cells in an IFN- and TNF- dependent manner. The responsiveness of TEMRA to IL-15 is not restricted to chronic stimulation as TEMRA from healthy volunteers respond earlier and faster when compared to EM. IL-15 induces anti-apoptotic signals and promotes proliferation dependent of PI3K/Akt, MAPK and ERK pathways. Without ex-vivo stimulation, TEMRA cells are metabolically more active than naive and EM, as shown by their high ATP reservoir and a high expression of genes involved in glycolysis, glutaminolysis and the Pentose Phosphate Pathway. Upon stimulation, TEMRA adapt their metabolism by sustaining an increased mitochondrial respiration and glycolysis. Finally, we show that the inhibition of glycolysis is highly effective in preventing endothelial inflammation induced by TEMRA from kidney transplant recipients. Together, our findings highlight the metabolic fitness that tightly regulates the immune function of TEMRA in physiological and pathogenic situations.